Activity-pH Relationship and Michaelis Constants during Activation of Profibrinolysin and during Fibrinogenolysis - Nanninga, L. B; Guest, M. M (Thrombosis and Haemostasis, 1968)
The pH dependence was investigated separately for the activation of Profibrinolysin by urokinase and for the breakdown of fibrinogen by fibrinolysin. The effects of concentration of the substrates, Profibrinolysin and fibrinogen, respectively, were investigated and Michaelis constants were estimated for both enzymatic reactions. The average concentration of Profibrinolysin in normal human plasma was found to be 1.4 × 10–6 M based on experiments with relatively pure Profibrinolysin.